(untitled) (Global Journal of Human-Social Science, 2012)
Recycling has been encouraged broadly as a tool to diminish the destructive impacts of excessive solid waste However recycling in most developing countries undergoes from lack of household participation The finding of this paper demonstrated that the major constraints that impede recycling involvement are likely to come from hidden cost of recycling the poor access of facility lack of recycling skill and unavailability of information